Characterization of product of pseudo-differential operators involving fractional fourier transform - Dubey J.K.; Pandey P.K.; Upadhyay S.K. (My University, 2025)
Characterizations of product of generalized pseudo-differential operators associated with symbol σ(x, ξ) ∈ Sm are discussed by exploiting the fractional Fourier transform. © Indian Mathematical Society, 2021.